2020
DOI: 10.1002/chem.202000603
|View full text |Cite
|
Sign up to set email alerts
|

Photoredox‐Mediated Reaction of gem‐Diborylalkenes: Reactivity Toward Diverse 1,1‐Bisborylalkanes

Abstract: Scheme2.Scope of the synthesis of gem-diborylalkanes, the proposed mechanism and ad euterium-labelling study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
39
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 39 publications
(55 citation statements)
references
References 61 publications
(34 reference statements)
0
39
0
Order By: Relevance
“…Recently, we reported a photoredox-mediated reaction of gem- diborylalkenes and showed that gem -diborylalkenes 2 have similar electron deficiency as vinylboron 1 ; hence, 2 should serve as a suitable dienophile for this type of cycloaddition reaction. However, key challenges include (1) the steric repulsion introduced by the two groups of the bulky Bpin units in the TS of the cycloaddition reaction; (2) whether the regio- and stereoselectivity of the cycloaddition can be controlled when two unsymmetrical boron groups are placed on the geminated carbon of dienophile 2′ ; and (3) whether the reaction can proceed in a regioselective manner when borylated dienes react with 2 (Figure B) …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, we reported a photoredox-mediated reaction of gem- diborylalkenes and showed that gem -diborylalkenes 2 have similar electron deficiency as vinylboron 1 ; hence, 2 should serve as a suitable dienophile for this type of cycloaddition reaction. However, key challenges include (1) the steric repulsion introduced by the two groups of the bulky Bpin units in the TS of the cycloaddition reaction; (2) whether the regio- and stereoselectivity of the cycloaddition can be controlled when two unsymmetrical boron groups are placed on the geminated carbon of dienophile 2′ ; and (3) whether the reaction can proceed in a regioselective manner when borylated dienes react with 2 (Figure B) …”
Section: Resultsmentioning
confidence: 99%
“…In recent years, gem -diboryl compounds 2 and 3′ have been widely adopted as coupling partners in synthetic chemistry. 11 , 20 For example, gem -diborylalkenes 2 have served as building blocks for Suzuki–Miyaura cross-coupling, nucleophilic partners, reduction approaches, Michael additions, 21 radical chemistry, 22 and other reactions. 13 , 23 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the [4+2] cycloaddition reactions of vinylboranates, 26 e.g., 1, are well documented in the literature (Figure 2A), [27][28][29][30] to the best of our knowledge, the use of gem-diboryllkenes (2) in these types of reactions is rare, despite the potential to provide new and efficient strategies to efficiently construct complex molecules (Figure 2B). 28,30 Recently, we reported a photoredox-mediated reaction of gemdiborylalkenes 31 and showed that gemdiboryalkenes (2) are more electron deficient compared to vinyl-boron 1; 31 hence, 2 should serve as a suitable dienophile for this type of cycloaddition reaction. However, key challenges include: (1) the steric repulsion introduced by the two groups of the bulky Bpin units in the TS of the cycloaddition reaction 32 (2) whether the regio-and stereoselectivity of the cycloaddition can be controlled when two unsymmetrical boron groups are placed on the geminated carbon of dienophile 2' 13 (3) whether the reaction can proceed in a regioselective manner when borylated dienes react with 2 (Figure 2B)?…”
Section: Resultsmentioning
confidence: 99%
“…Although the [4+2] cycloaddition reactions of vinylboranates, 26 e.g., 1, are well documented in the literature (Figure 2A), [27][28][29][30] to the best of our knowledge, the use of gem-diboryllkenes (2) in these types of reactions is rare, despite the potential to provide new and efficient strategies to efficiently construct complex molecules (Figure 2B). 28,30 Recently, we reported a photoredox-mediated reaction of gemdiborylalkenes 31 and showed that gemdiboryalkenes (2) are more electron deficient compared to vinyl-boron 1; 31 hence, 2 should serve as a suitable dienophile for this type of cycloaddition reaction. However, key challenges include: (1) the steric repulsion introduced by the two groups of the bulky Bpin units in the TS of the cycloaddition reaction 32 (2) whether the regio-and stereoselectivity of the cycloaddition can be controlled when two unsymmetrical boron groups are placed on the geminated carbon of dienophile 2' 13 (3) whether the reaction can proceed in a regioselective manner when borylated dienes react with 2 (Figure 2B)?…”
Section: Resultsmentioning
confidence: 99%